Gempur Stunting dengan “Mie Aylor” di Desa Lewopao Kecamatan Ile Boleng - Reinaldis Masi; Mudmainna Mudmainna; Brigita Elisabet KR. Uran (Pusat Riset dan Inovasi Nasional, 2025)
Stunting is a chronic nutritional problem that is still a public health challenge in various regions of Indonesia, including Lewopao Village, Ile Boleng District. This community service activity aims to educate the public about the importance of balanced nutrition and efforts to prevent stunting through nutritious local food innovations. One of the innovations introduced is